Ancient grasslands guide ambitious goals in grassland restoration - Buisson, Elise; Archibald, Sally; Fidelis, Alessandra [UNESP]; Suding, Katharine N. (American Association for the Advancement of Science (AAAS), 2022)
Grasslands, which constitute almost 40% of the terrestrial biosphere, provide habitat for a great diversity of animals and plants and contribute to the livelihoods of more than 1 billion people worldwide. Whereas the destruction and degradation of grasslands can occur rapidly, recent work indicates that complete recovery of biodiversity and essential functions occurs slowly or not at all. Grassland restoration—interventions to speed or guide this recovery—has received less attention than restoration of forested ecosystems, often due to the prevailing assumption that grasslands are recently formed habitats that can reassemble quickly. Viewing grassland restoration as long-term assembly toward old-growth endpoints, with appreciation of feedbacks and threshold shifts, will be crucial for recognizing when and how restoration can guide recovery of this globally important ecosystem.